Advanced treatment of chicken farm flushing wastewater by integrating Fenton oxidation and algal cultivation process for algal growth and nutrients removal. (15th November 2021) - Cui, Hongli; Yu, Jie; Zhu, Xiaoli; Cui, Yulin; Ji, Chunli; Zhang, Chunhui; Xue, Jinai; Jia, Xiaoyun; Qin, Song; Li, Runzhi
Abstract: Algae based wastewater treatment has been considered as the most promising win-win strategy for nutrients removal and biomass accumulation. However, the poor linking between traditional wastewater treatment and algal cultivation limits the achievement of this goal. In this study, a novel combination of Fenton oxidation and algal cultivation (CFOAC) system was investigated for the treatment of chicken farm flushing wastewater (CFFW). Fenton oxidation (FO) was adopted to reduce the excessive ammonia nitrogen, which might inhibit the algal growth. The results showed that single FO pretreatment removed 70.5 %, 96.7 %, 86.1 %, and 96.2 % of TN, TAN, TP, and COD, respectively. The highest biomass (235.8 mg/L/d) and lipid (77.3 mg/L/d) productivities were achieved on optimized CFOAC system after 7 days batch cultivation. Accordingly, the nutrients removal efficiencies increased to almost 100 %. Further fatty acid profile analysis showed that algae grown on optimal CFOAC system accumulated a high level of total lipids (32.8 %) with C16–C18 fatty acid as the most abundant compositions (accounting for over 60.6 %), which were propitious to biodiesel production. In addition, this CFOAC system was magnified from 1 L flask to 50 L horizontal pipe photobioreactor (HPPB) in semi-continuously culture under optimal conditions. The average biomass and lipid productivities were 995.7 mg/L/d and 320.6 mg/L/d, respectively, when cultured at 6 days hydraulic retention time with 1/3 substitution every two days. These findings proved that the novel CFOAC system is efficient in nutrients removal, algal cultivation, and biomass production for advanced treatment of CFFW. Graphical abstract: Image 1 Highlights: Combined Fenton oxidation and algal cultivation (CFOAC) system was investigated. Fenton oxidation could reduce TN, TAN, TP and COD contents and improve algal growth. High biomass and lipid productivities were obtained on 7 days batch CFOAC system. Almost all TN, TAN, and TP nutrients were removed on 7 days batch CFOAC system. The CFOAC system is efficient to algal biomass production and nutrients removal.